Pengaruh Permainan Tradisional Egrang Tempurung Kelapa Terhadap Keseimbangan Anak Usia Dini 4 - 6 Tahun - Rahim, Anita Faradilla; , Agus Widodo, S.Fis., M.Fis; , Maskun Pudjianto, M.Kes (2015)
Background: Balance is the ability of the body to look after its posture to be erect and to defend its position whether in static or dynamic condition. Underage children experience very fast development so that it is better to give stimulations for them. One of the stimulations which can be given to the underage children is coconut shield Egrang traditional game. When the children are playing coconut shield Egrang their muscles contractions will build up, especially its lower extremities and abdomen so that the muscles strength will be increased. Therefore, coconut shield Egrang traditional game can be applied as balancing exercise program. Purpose: To find out the influence of coconut shield Egrang traditional game towards the balances children ages 4-6. The research method: This research is quasi-experimental research with pre and post test design with control group as an approach. The number of respondents in this research is 60 people, with 30 people as treatment group and 30 as control group. This research is conducted in three times a week for a month with 10 minutes durations in every session. Stork stand test for static balance and balance beam test for dynamic balance methods are applied to measure the balance. The result of the research: By applying coconut shield Egrang traditional game treatment for treatment group, there are 30 respondents (100%) who are experiencing the increase of static and dynamic balances significantly. Conclusion: there are significant influences of coconut shield Egrang traditional game treatment towards the balances of children ages 4-6.